2021
DOI: 10.1186/s12920-021-00953-8
|View full text |Cite
|
Sign up to set email alerts
|

Gene variants associated with acne vulgaris presentation and severity: a systematic review and meta-analysis

Abstract: Background Multiple factors have been attributed to acne vulgaris predisposition and individual variations in the severity of skin symptoms, and genetics stood out as one of the major factors. Methods We performed a systematic review on the genes and their variants that have been investigated for association with acne presentation and severity. A random-effect meta-analysis using the allele model (minor allele vs. major allele) was also conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 94 publications
4
36
0
Order By: Relevance
“…For example, a population‐based study in the USA showed that the disease burden for patient with light‐coloured skin is heavier 30 . Moreover, a recent systematic review on gene variants implicated in acne vulgaris reported that genes for immune and inflammatory response, especially tumour necrosis factor, and genes for sebaceous gland function and activity, CYP17A1 and FST in particular, were associated with acne presentation and severity 31 . Similar to almost all studies of global epidemiological burden, the heterogeneity in healthcare services, diagnostic methods, diagnostic evaluation standards, and dermatologists’ insights in these countries and even subnational regions could influence both the geographical differences and the temporal trends.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a population‐based study in the USA showed that the disease burden for patient with light‐coloured skin is heavier 30 . Moreover, a recent systematic review on gene variants implicated in acne vulgaris reported that genes for immune and inflammatory response, especially tumour necrosis factor, and genes for sebaceous gland function and activity, CYP17A1 and FST in particular, were associated with acne presentation and severity 31 . Similar to almost all studies of global epidemiological burden, the heterogeneity in healthcare services, diagnostic methods, diagnostic evaluation standards, and dermatologists’ insights in these countries and even subnational regions could influence both the geographical differences and the temporal trends.…”
Section: Discussionmentioning
confidence: 99%
“…Acne vulgaris is a disease for which its occurrence and severity depend on various factors. These include, e.g., demographic, diet and lifestyle, and hormonal and genetic factors [ 47 ]. Current scientific reports on genes related to clinical symptoms and acne severity are scarce.…”
Section: Genetic Factors In Pathogenesis Acne Vulgarismentioning
confidence: 99%
“…Recent genome-wide studies have shown that genes associated with acne influence sebaceous gland functions or the development of an inflammatory immune response [ 48 , 49 ]. The TNF gene variants located on chromosome 6p21.33 are the most frequently studied genes in terms of the severity of acne lesions caused by pro-inflammatory immune responses [ 47 ]. The studies present that the crucial variants are variability in positions -308, -238, -863, -857, and -1031 TNF SNP in acne [ 50 , 51 ].…”
Section: Genetic Factors In Pathogenesis Acne Vulgarismentioning
confidence: 99%
See 2 more Smart Citations